2018
DOI: 10.1016/j.leukres.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with a prolonged hospital stay during induction chemotherapy in newly diagnosed high risk pediatric acute lymphoblastic leukemia

Abstract: A significant proportion of newly diagnosed HR or VHR pediatric ALL patients experience a prolonged LOS and unplanned re-admissions. Aggressive discharge planning and close follow up is indicated in this cohort of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Readmission for nontreatment therapy was from 18.5% to 33.3% depending on outcome definitions (e.g., nonelective, unplanned, or unintentional readmission). These results are comparable with previous studies, with 30-day readmission ranging from 23% to 36% [7,23,24]. The top three reasons for readmission were neutropenia/agranulocytosis (27.8%), septicemia (15.3%), and pancytopenia (11.5%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Readmission for nontreatment therapy was from 18.5% to 33.3% depending on outcome definitions (e.g., nonelective, unplanned, or unintentional readmission). These results are comparable with previous studies, with 30-day readmission ranging from 23% to 36% [7,23,24]. The top three reasons for readmission were neutropenia/agranulocytosis (27.8%), septicemia (15.3%), and pancytopenia (11.5%).…”
Section: Discussionsupporting
confidence: 89%
“…This finding is supported by a study by Wedekind et al [7], who showed a longer length of stay is associated with decreased risk of readmission (OR 0.44, 95%CI 0.35-0.56) vs. a short length of stay during induction therapy in newly diagnosed ALL children. In contrast, Warrick et al [23] recommended aggressive discharge plans during induction chemotherapy for newly diagnosed high/very high risk ALL pediatric patients because of no difference in the likelihood of readmission. This discrepancy between Wedekind et al (using a U.S. national representative sample) and Warrick et al (using an institutional sample) could be due to the difference in the quality of care among hospitals or coding practice among hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…8,21 Prolonged hospital stay could be due to organ dysfunction, infectious or metabolic complications. 22 The duration of induction was significantly longer in the malnourished compared to the wellnourished group. Another study also found that the majority of ALL children who did not complete chemotherapy on time were severely malnourished.…”
Section: Discussionmentioning
confidence: 89%
“…The pooled prevalence of VRE colonization among patients with hematological malignancies was 24% (95% CI, 16%–34%) [ 29 ], which is similar to the values detected in this study. The increased risk in the hematology-oncology wards might also be associated with an ongoing exposure to healthcare environments due to prolonged hospital stay and readmission and with more frequent antimicrobial treatment due to febrile neutropenia [ 32 ]. Clinical practice guidelines recommend cefepime (4th cephalosporin generation) as the initial antibiotic monotherapy, while fluoroquinolones prophylaxis is recommended for all high-risk hematological patients [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%